ANALISIS OPTIMASI WAKTU DAN BIAYA PADA PROYEK REHABILITASI SARANA DAN PRASARANA GEDUNG SEKOLAH DENGAN METODE TIME COST TRADE OFF - Irra Purnomo, Amellia Intan Putri; Yulianto, Totok; Nugroho, Meriana Wahyu; Sundari, Tiitin (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Hasyim Asy'ari, 2025)
Completion of delays in the implementation of field control requires alternative analysis to get the results of accelerated time that has an impact on minimum costs. This study uses the Time Cost Trade Off (TCTO) method which aims to determine the optimization of time and cost in the rehabilitation project of facilities and infrastructure for the Mojoduwur 1 Jombang Elementary School building. This method is applied by evaluating various acceleration alternatives, one of which is through the addition of time and labor on critical path activities. The results of the analysis show that the most optimal acceleration alternative is the application of 3-shift working time which is able to accelerate the project duration for 51 days or 69 days of acceleration from 120 days of normal duration. The total cost savings reached Rp25,915,887 or Rp545,155,547 from the normal cost of Rp571,071,434, thus obtaining a time efficiency of 42.5% and a cost efficiency of 4.54%. The TCTO approach with the implementation of shift work can improve the time and cost efficiency of this project.